The efficacy and safety of a homoharringtonine-based protocol for children with acute myeloid leukemia: A retrospective study in China. (23rd September 2020) - Tang, Yanjing; Luo, Chengjuan; Shen, Shuhong; Xue, Huiliang; Pan, Ci; Hu, Wenting; Chen, Xiaoxiao; Cai, Jiaoyang; Chen, Jing; Tang, Jingyan
Abstract: The standard chemotherapy for acute myeloid leukemia (AML) is usually composed of anthracyclines and cytarabine. We previously reported that homoharringtonine (HHT) was incorporated into regimens for pediatric AML with acceptable efficacy and tolerable toxicity. We treated newly diagnosed AML patients aged 0–18 years on the AML-SCMC-2009 protocol. A total of 102 de novo newly diagnosed AML patients aged 0–18 years were enrolled. All patients were treated with ten courses of chemotherapy including double induction, high dose cytarabine consolidation, and maintenance. The cumulative dose of HHT was 165 mg/m 2 and the daunorubicin dose was 120 mg/m 2 . Complete remission (CR), overall survival (OS) rate, event free survival (EFS) rate, adverse effect response and prognosis factors were retrospectively evaluated to investigate the long-term outcome and safety of this protocol. Eighty-two patients (80.4%) achieved complete remission with the first induction. The 5-year overall survival and event-free survival rates were 65.0% ( SE, 4.9%) and 53.3% ( SE, 5.2%), respectively. A first induction failure, age older than 2 years, and BCR-ABL translocation were associated with a significantly worse outcome ( p < 0.05). No significant drug-related cardiac toxicity was observed. AML-SCMC-2009 protocol which use HHT as backbone drug is efficacious and tolerated. HHT could partially replace anthracycline to be an effective option for childhood AML.